Correlation between mammal track abundance and Forest Landscape Integrity Index validates actual forest ecological integrity - Malcangi, Francesca; Lindén, Andreas; Sundell, Janne; Loehr, John (Springer Nature, 2024)
Human disturbance compromises the ecological integrity of forests, negatively affecting associated species. Assessing the impact of forest integrity on biodiversity is complex due to the interplay of various human activities, ecological factors, and their interactions. Current large-scale indices assess forest integrity but often lack a direct connection to the biotic environment. We tested the effectiveness of the global Forest Landscape Integrity Index (FLII) in evaluating aspects of anthropogenic forest degradation on the biotic community. We analyzed the relationship between changes in the ecological integrity of Finnish forests and variations in mammal species abundance, using the number of tracks from 17 different species collected during the winter seasons between 2016 and 2020 in south-central Finland. Beyond the FLII, we analyzed forest and canopy cover to enhance the accuracy of habitat preference assessments. We found that the FLII captures the varying degrees of forest integrity, as reflected by the correlation between the abundance of winter tracks and the FLII for most mammals. Species that were positively associated with forest integrity were all native to the boreal forest, while mammals that adapt well to human-disturbed environments including two invasive species were more common in lower FLII forests. Significant differences in habitat preferences were also observed in relation to forest and canopy cover, revealing additional nuances that the FLII alone did not capture. This study demonstrates that the FLII, when combined with a comprehensive dataset and supplemented with region-specific factors, can assess species' adaptability to human-modified forests, aiding in the development of conservation strategies.
Keywords: Ecological integrity; Habitat loss; Boreal forest; Mammals; Native species